Measuring within-winter movement rates of Tufted Duck Aythya fuligula and Common Pochard A. ferina based on ring re-encounter data - Korner-Nievergelt, Fränzi R; Hofer, Josef; Sauter, Annette; Jenni, Lukas (Wildfowl, 2009)
Within-winter movements of birds are of interest for the identification of subpopulations and for the assessment of the risk of bird-transmitted diseases. The probability of a Tufted Duck Aythya fuligula or a Common Pochard A. ferina wintering in the Alpine region leaving this area during winter was estimated from capture and ring re-encounter data. A multi-state model was used to estimate this movement probability for each two-week period. Bias and precision of parameter estimates of the multi-state model were assessed using simulated data. These simulations indicated that there was a low level of bias in the estimated movement probabilities, but that precision levels were also low. The probability of Tufted Duck and Common Pochard moving >200 km from the ringing site within a two-week period after ringing was estimated at around 90% for both species. Although the precision of this estimate was low, by presenting the first quantitative measures of individual diving duck movements between the Alpine region and the rest of the Europe, the study contributes to an understanding of the within-winter dispersal of ducks across Europe.